Development of an Automatic Analyzer for Monitoring Hydrogen Sulfide (International Journal of Psychosocial Rehabilitation, 2020)
Selective thermos-catalytic sensors have been developed, and gas analyzers have been created based on them, which determine hydrogen sulfide in a wide range of its concentrations. The manufactured analyzers are distinguished by high sensitivity, selectivity, and quick action, as well as reliability and performance under harsh and extreme conditions (pressure and temperature changes over a wide range). The created analyzers will find wide application in solving important social, environmental, and economic problems of monitoring environmental objects and the safe functioning of a number of explosion-hazardous industries.